A study on the factor effecting project delay in the housing construction - Fatin Fazlinda, Hamzah (2016)
This research is about the factor effecting project delay in housing construction. The purpose of this study is to identify factor delay in the housing project, to find out lack of fund to finance the project to completion effected on project delay, to investigate mistakes during construction and project management problem influence on project delay and to identify subcontractor delays effected project delay. Besides that, this study focuses on construction industries at Kuantan. The technique to study this project is I’m use a method with distributes the questionnaire to people who related on this study. I distribute the questionnaire to 66 respondents on Kota Sas Company. After I’m distribute the questionnaire, I use the Statistical Package for the Social Sciences (SPSS) software to analyze the data to get the result. The specific implication from the finding reported in this study can be grouped into four category, compensation, need for achievement, equality theory and job performance.